PENAMPILAN REPRODUKSI INDUK TERNAK BABI DI KECAMATAN TELUK AMBON - Lumahmina, Winda; Souhoka, Demianus; Siwa, Isak (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
The development of the livestock sub-sector is a crucial component of the national agricultural sector's progress. This study aims to evaluate the performance of the reproductive system of pig breeders in Teluk Ambon District. The method employed in this study is a survey method, involving data collection from all pig farmers (census) in the Ambon District area. The variables observed in this study pertain to the population structure and reproductive performance of pig breeders, including the age of sexual maturity, age at first mating, signs of estrus, duration of estrus, estrus cycle, mating pattern, gestation period, calving interval, litter size, and pre-weaning mortality, with their respective operational definitions. The study results concluded that the age at first mating was 8.95 ± 1.29 months, the age at first calving was 12.95 ± 1.29 months, the gestation period was 115.5 ± 2.93 days, the litter size was 5.16 ± 3.04, the calving interval was 8.36 ± 1.86 months, and the mortality rate was 0.31 ± 0.70. The signs of estrus observed included being silent when mounted, restlessness, decreased appetite, and a red and swollen vulva.